Cubic boron nitride sintered body and method of manufacturing the same, and tool

KR103021801B1Active Publication Date: 2026-09-18RESONAC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020267022045
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-07-19
Filing Date
2025-07-16
Publication Date
2026-09-18
Estimated Expiration
2045-07-16

Smart Images

  • Figure 112026082860455-PCT00007_ABST
    Figure 112026082860455-PCT00007_ABST
Patent Text Reader

Abstract

A cubic boron nitride sintered body having cubic boron nitride and a binder phase which is the remainder of the cubic boron nitride, wherein the content of the cubic boron nitride is 50.0 to 90.0 volume%, and the binder phase contains one or more selected from the group consisting of Ti carbides, Ti nitrides, Ti carbonitrides, and Ti borides, and one or more selected from the group consisting of W2B and W2CoB2, and in the X-ray diffraction pattern of the cubic boron nitride sintered body using CuKα rays as a source, wherein the intensity of the diffraction peak attributed to the (111) plane of the cubic boron nitride is IA, the intensity of the diffraction peak attributed to the (211) plane of the W2B is IB, and the intensity of the diffraction peak with the greater intensity among the diffraction peak attributed to the (211) plane and the diffraction peak attributed to the (310) plane of the W2CoB2 When referred to as Ic, the ratio of the sum of IB and IC to IA [(IB+IC) / IA] is 0.25 or higher, and there is provided a cubic boron nitride sintered body, a method for manufacturing the same, and a tool.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present embodiment relates to a cubic boron nitride sintered body, a method for manufacturing the same, and a tool. Background Technology

[0002] Cubic boron nitride (hereinafter also referred to as "cBN") is a material with hardness comparable to that of diamond, and cBN sintered bodies, formed by sintering cBN particles as the main component, are materials that possess both wear resistance and fracture resistance. For this reason, cBN sintered bodies are primarily used in cutting tools for difficult-to-machine materials such as high-hardness steel. Furthermore, improvements to cBN sintered bodies are being made to meet the demand for further enhancement of fracture resistance, depending on the purpose of the machining process and the various usage modes of the cutting tool.

[0003] For example, Patent Document 1 describes a cBN sintered body having excellent strength and heat resistance by setting the weight ratio of W to the total weight of W, Co, and Ni to 0.2 to 0.6 and the weight ratio of Co to the total weight of Co and Ni to 0.6 to 0.95 for the metal components W, Co, and Ni present as compounds in the cBN sintered body. Prior art literature

[0004] International Publication No. 2000 / 047537 The problem to be solved

[0005] However, recently, due to the increasing difficulty of machining workpieces to accommodate lightweighting and the significant increase in cutting speeds to reduce machining costs, the performance requirements for tools using cBN sintered bodies (hereinafter also referred to as "cBN tools") are becoming stricter.

[0006] The present embodiment aims to provide a cBN sintered body with excellent fracture resistance, a method for manufacturing the same, and a tool, taking into account the current situation. means of solving the problem

[0007] The inventors, etc., have conducted extensive research to solve the above problem and have found that the above problem can be solved by the present embodiment below.

[0008] [1] A cubic boron nitride sintered body having a cubic boron nitride and a binder phase which is the remainder of the cubic boron nitride,

[0009] The content of the above cubic boron nitride is 50.0 to 90.0 volume%, and

[0010] The above-mentioned binding phase contains one or more selected from the group consisting of Ti carbides, Ti nitrides, Ti carbonitrides, and Ti borides, and one or more selected from the group consisting of W2B and W2CoB2, and

[0011] In the X-ray diffraction pattern of the above-mentioned cubic boron nitride sintered body using CuKα rays as a source,

[0012] The intensity of the diffraction peak attributed to the (111) plane of the above cubic boron nitride is I A ,

[0013] The intensity of the diffraction peak attributed to the (211) plane of the above W2B is I B ,

[0014] The intensity of the diffraction peak attributable to the (211) plane and the diffraction peak attributable to the (310) plane of the above W2CoB2, the intensity of the diffraction peak with the greater intensity is I c When saying,

[0015] The above I A Regarding, the above I B and the above I C The ratio of the sum of [(I B +I C ) / I A Cubic boron nitride sintered body having ] 0.25 or higher.

[0016] [2] A cubic boron nitride sintered body described in [1] above, having a W content of 4.00 to 15.00 mass%.

[0017] [3] The above I CRegarding the above I B The ratio of [I B / I C A cubic boron nitride sintered body described in [1] or [2] above, wherein ] is 0.20 to 1.00.

[0018] [4] Average particle diameter (D 50 A cubic boron nitride sintered body described in any one of [1] to [3] containing two or more different types of cubic boron nitride particles.

[0019] [5] A cubic boron nitride sintered body described in any one of [1] to [4] above, having a thermal conductivity of 50.0 W / m·K or higher.

[0020] [6] A tool comprising a cubic boron nitride sintered body as a constituent material as described in any one of [1] to [5] above.

[0021] [7] The tool described in [6] above for cutting or grinding.

[0022] [8] A method for manufacturing a cubic boron nitride sintered body as described in any one of [1] to [5] above,

[0023] A binder grinding process in which a binder, which is a raw material forming the above-mentioned bonding phase, is ground in a container containing a grinding medium, and

[0024] A mixing process for obtaining a raw material mixture by mixing the binder after grinding and cubic boron nitride particles, and

[0025] The process includes a sintering process for obtaining a cubic boron nitride sintered body by pressurizing and heating the above raw material mixture, and

[0026] A method for manufacturing a cubic boron nitride sintered body in which the grinding medium used in the above-mentioned binder grinding process contains WC. Effects of the invention

[0027] According to the present embodiment, a cBN sintered body with excellent fracture resistance, a method for manufacturing the same, and a tool can be provided. Brief explanation of the drawing

[0028] Figure 1 is the XRD pattern of the cBN sintered body obtained in Example 1. Figure 2 is the XRD pattern of the cBN sintered body obtained in Comparative Example 2. Figure 3 is a reflected electron image (magnification 5,000x) of the cBN sintered body obtained in Example 1 by a scanning electron microscope (SEM). Figure 4 is the binarization processing phase of the reflected electron image shown in Figure 3. Specific details for implementing the invention

[0029] In this specification, a numerical range indicated by "~" represents a range that includes the values ​​listed before and after "~" as the minimum and maximum values, respectively.

[0030] For example, the notation “X to Y” (where X and Y are real numbers) refers to a numerical range greater than or equal to X and less than or equal to Y. Furthermore, the description “greater than or equal to X” in this specification refers to X and a value greater than X. Additionally, the description “less than or equal to Y” in this specification refers to Y and a value less than Y.

[0031] The lower and upper limits of the numerical ranges described in this specification may be arbitrarily combined with the lower or upper limits of other numerical ranges.

[0032] In the numerical ranges described in this specification, the lower or upper limit of the numerical range may be replaced with the values ​​shown in the examples.

[0033] Each component and material exemplified in this specification may be used alone or in combination of two or more types, unless specifically mentioned otherwise.

[0034] In the present specification, when only one element symbol is written alone, such as "W", the valence and state of the element are not limited and refer to both the element forming a compound and the element in a metallic state. Meanwhile, for an element in a metallic state with zero valence, "metal" is placed before the element symbol, such as "metal W".

[0035] Each component and material exemplified in this specification may be used alone or in combination of two or more types, unless specifically mentioned otherwise.

[0036] The expression “containing XX” as described in this specification includes both meanings: containing XX in a reacted state where XX can react, and simply containing XX.

[0037] The mechanisms of action described in this specification are conjectures and do not limit the mechanisms demonstrating the effects of the present embodiment.

[0038] An embodiment comprising any combination of the details described in this specification is also included in this embodiment.

[0039] [Cubic Boron Nitride Sintered Body]

[0040] The cubic boron nitride sintered body of the present embodiment is,

[0041] A cubic boron nitride sintered body having a cubic boron nitride and a binding phase which is the remainder of the cubic boron nitride,

[0042] The content of the above cubic boron nitride is 50.0 to 90.0 volume%, and

[0043] The above-mentioned binding phase contains one or more selected from the group consisting of Ti carbides, Ti nitrides, Ti carbonitrides, and Ti borides, and one or more selected from the group consisting of W2B and W2CoB2, and

[0044] In the X-ray diffraction pattern of the above-mentioned cubic boron nitride sintered body using CuKα rays as a source,

[0045] The intensity of the diffraction peak attributed to the (111) plane of the above cubic boron nitride is I A ,

[0046] The intensity of the diffraction peak attributed to the (211) plane of the above W2B is I B ,

[0047] The intensity of the diffraction peak attributable to the (211) plane and the diffraction peak attributable to the (310) plane of the above W2CoB2, the intensity of the diffraction peak with the greater intensity is I c When saying,

[0048] The above I A Regarding, the above I B and the above I C The ratio of the sum of [(I B +I C ) / I A It is a cubic boron nitride sintered body with a value of 0.25 or higher.

[0049] <cbn>

[0050] The content of cBN in the cBN sintered body of the present embodiment is 50.0 to 90.0 volume%, preferably 55.0 to 89.0 volume%, more preferably 63.0 to 88.0 volume%, even more preferably 68.0 to 87.0 volume%, preferably 73.0 to 85.0 volume%, more preferably 75.0 to 82.0 volume%, and even more preferably 76.0 to 80.0 volume%.

[0051] If the cBN content is 50.0 volume% or more, excellent properties of cBN such as high hardness, high oxidation resistance, and high thermal conductivity are utilized, and even if minute cracks occur, the propagation of cracks into the interior of the cBN sintered body is suppressed, thereby obtaining good fracture resistance. In addition, if the cBN content is 90.0 volume% or less, aggregation of cBNs is suppressed, and since cBNs do not detach and sinter easily, good wear resistance is obtained.

[0052] In addition, the cBN content in the cBN sintered body is a value in which the ratio of the occupied area of ​​cBN in the scanning electron microscope (SEM) image of the polished surface of the cBN sintered body is considered as the volume content, and specifically, it can be obtained by the method described in the example.

[0053] The average value of the ferret diameter measured from the cross-sectional SEM image of the cBN included in the cBN sintered body of the present embodiment is preferably 0.3 to 8.0 μm, more preferably 0.4 to 5.0 μm, and even more preferably 0.5 to 2.0 μm.

[0054] If the average value of the ferret diameter of the cBN is greater than or equal to the lower limit, the cBN tends to be firmly maintained by the bonding phase. Additionally, if the average value of the ferret diameter of the cBN is less than or equal to the upper limit, the fracture toughness of the cBN sintered body tends to be excellent.

[0055] Also, in this specification, "ferret diameter" means the longest distance among straight lines connecting any two points on the outer circumference of the cBN cross-section observed in the cross-sectional photograph of the cBN sintered body.

[0056] The average value of the cBN ferret diameter is obtained by determining all measurable cBN ferret diameters across the entire field of view of a 5,000x magnification scanning electron microscope (SEM) of the polished surface of the cBN sintered body, and calculating the arithmetic mean thereof. Specifically, it can be obtained by the method described in the example.

[0057] The cBN particles used in the manufacture of the cBN sintered body of the present embodiment preferably have a small porosity from the perspective of improving the thermal conductivity of the cBN sintered body and further enhancing wear resistance and defect resistance.

[0058] In addition, the term “porosity of cBN particles” in this specification refers to the porosity calculated from only the cBN particles used in the manufacture of the cBN sintered body, and in the case where only one type of cBN particle is used, it refers to the porosity of the said one type of cBN particle, and in the case where two or more types of cBN particles are used, it refers to the porosity of the mixture of said two or more types of cBN particles.

[0059] The porosity of cBN particles can be calculated from the particle size distribution of cBN particles using the following Ouchiyama formula. Furthermore, the Ouchiyama formula is described in detail in the following literature.

[0060] N. Ouchiyama and T. Tanaka, Ind. Eng. Chem. Fundam., 19, 338 (1980)

[0061] N. Ouchiyama and T. Tanaka, Ind. Eng. Chem. Fundam., 20, 66 (1981)

[0062] N. Ouchiyama and T. Tanaka, Ind. Eng. Chem. Fundam., 23, 490 (1984)

[0063]

[0064]

[0065]

[0066]

[0067]

[0068] The porosity of the cBN particles calculated using the above Ouchiyama formula is preferably 50 volume% or less, more preferably 45 volume% or less, even more preferably 40 volume% or less, even more preferably 37 volume% or less, and particularly preferably 35 volume% or less.

[0069] If the porosity of the cBN particles is below the upper limit, the cBN sintered body of the present embodiment tends to have superior thermal conductivity, wear resistance, and fracture resistance.

[0070] The porosity of the above cBN particles is preferably smaller, but from the perspective of ease of manufacturing, it may be 10 volume% or more, 20 volume% or more, or 25 volume% or more.

[0071] A more detailed method for calculating the porosity of cBN particles using the above Ouchiyama formula is as described in the examples.

[0072] In order to reduce the above porosity and further improve the thermal conductivity, wear resistance, and defect resistance of the cBN sintered body, the cBN sintered body of the present embodiment has an average particle diameter (D 50 It is preferable to contain two or more types of cBN particles with different values, and the average particle diameter (D 50 It is more preferable that it contains three or more types of cBN particles that are different from each other.

[0073] In addition, the average particle diameter (D) contained in the cBN sintered body of the present embodiment 50 The types of different cBN particles may be 6 or fewer, 5 or fewer, or 4 or fewer.

[0074] Also, in this specification, the average particle diameter (D 50 ) refers to the particle diameter at 50% of the cumulative volume in the volume distribution of particle diameters measured by laser diffraction scattering. Average particle diameter (D 50 ) can be measured by the method described in the examples.

[0075] Average particle diameter (D 50 Among two or more types of cBN particles with different values, the average particle diameter (D 50 The average particle diameter (D) of the two types of cBN particles with the smallest difference 50 The difference of ) is preferably 0.5 to 3.0 μm, more preferably 1.0 to 2.0 μm, and even more preferably 1.4 to 1.8 μm.

[0076] In addition, the average particle diameter (D 50 Among two or more types of cBN particles with different characteristics, the maximum average particle diameter (D 50 cBN particles having ) and minimum average particle diameter (D 50 Average particle diameter (D) of cBN particles having ) 50 The difference of ) is preferably 1.0 to 6.0 μm, more preferably 2.0 to 5.0 μm, and even more preferably 3.0 to 4.0 μm.

[0077] Average particle diameter (D 50 If ) contains two or more types of cBN particles that are different from each other, the average particle diameter (D) of the two or more types of cBN particles 50 Each is preferably selected from a range of 0.1 to 10.0 μm, more preferably 0.4 to 7.0 μm, and even more preferably 0.6 to 5.0 μm.

[0078] In terms of reducing the above porosity, the average particle diameter (D 50 Two or more types of cBN particles with different ) are, for example, average particle diameter (D 50 cBN particles (1) with a diameter of 0㎛ or more and less than 2.0㎛, and an average particle diameter (D 50 cBN particles (2) with a diameter of 2.0㎛ or more and less than 4.0㎛, and an average particle diameter (D 50 It is preferable to contain two or three types of cBN particles (3) with a size of 4.0㎛ or more and less than 6.0㎛.

[0079] When the above cBN particles (1), the above cBN particles (2) and the above cBN particles (3) are included, the content of the above cBN particles (1) is preferably 5 to 35 mass%, more preferably 10 to 30 mass%, and even more preferably 15 to 25 mass% with respect to the total content of the cBN particles (100 mass%).

[0080] When the above cBN particles (1), the above cBN particles (2) and the above cBN particles (3) are included, the content of the above cBN particles (2) is preferably 55 to 85 mass%, more preferably 60 to 80 mass%, and even more preferably 65 to 75 mass% with respect to the total content of the cBN particles (100 mass%).

[0081] When the above cBN particles (1), the above cBN particles (2) and the above cBN particles (3) are included, the content of the above cBN particles (3) is preferably 2 to 25 mass%, more preferably 3 to 20 mass%, and even more preferably 5 to 15 mass% with respect to the total content of the cBN particles (100 mass%).

[0082] <Combination>

[0083] The bonding phase is a phase corresponding to the remainder of the cBN in the cBN sintered body of the present embodiment.

[0084] The binding phase contains one or more selected from the group consisting of Ti carbides, Ti nitrides, Ti carbonitrides and Ti borides, and one or more selected from the group consisting of W2B and W2CoB2.

[0085] The cBN sintered body of the present embodiment, in an X-ray diffraction pattern using CuKα rays as a source,

[0086] The intensity of the diffraction peak attributed to the (111) plane of cBN is I A ,

[0087] The intensity of the diffraction peak attributed to the (211) plane of W2B is I B ,

[0088] The intensity of the diffraction peak attributable to the (211) plane of W2CoB2 and the diffraction peak attributable to the (310) plane of W2CoB2, whichever has a larger intensity, is I c When saying,

[0089] I A Regarding, I B and I C The ratio of the sum of [(I B +I C ) / I A ] is 0.25 or higher.

[0090] The cBN sintered body of the present embodiment is the above non-[(I B +I C Since ) / IA] is 0.25 or higher, fracture toughness is improved and fracture resistance is excellent. The reason for this is not certain, but it is estimated as follows.

[0091] Since W2B and W2CoB2 included in the cBN sintered body of the present embodiment are easily formed from fine W atoms, the above [(I B +I C ) / I A It is expected that the cBN sintered body of the present embodiment, in which ] is 0.25 or higher, contains a large amount of minute W2B and W2CoB2. And, since the above W2B and W2CoB2 have properties that make it difficult for cracks to propagate, the cBN sintered body of the present embodiment has excellent fracture toughness, and thus is thought to have excellent fracture resistance.

[0092] Intensity I of the above diffraction peak A , I B , I C and I described below D The XRD pattern of the cBN sintered body to be obtained can be acquired by the method described in the example. The measured XRD pattern of the cBN sintered body can be compared with an inorganic material database to qualitatively determine the contained components and to acquire the diffraction peak intensity of each component. The qualitative determination and acquisition of diffraction peak intensity can be performed using commercially available software. For example, the software "X'pert High Score Plus" manufactured by PANalytical can be used.

[0093] In addition, in this embodiment, W2CoB2 may also be denoted as B2CoW2 in addition to W2CoB2 in the inorganic material database. Furthermore, since the angle of appearance of the diffraction peaks is close to the (211) plane of W2CoB2 and the (310) plane of W2CoB2, the peaks belong to at least one of the (211) plane of W2CoB2 and the (310) plane of W2CoB2. If it is not possible to determine which plane the peak belongs to, the peak is defined as "the one with the greater intensity among the diffraction peaks belonging to the (211) plane of W2CoB2 and the diffraction peaks belonging to the (310) plane of W2CoB2."

[0094] The above [(I B +I C ) / I A ] is preferably 0.30 to 4.00, more preferably 0.40 to 3.00, even more preferably 0.50 to 2.50, even more preferably 0.60 to 2.00, even more preferably 0.70 to 1.60, even more preferably 0.80 to 1.40, and particularly preferably 0.90 to 1.20, in order to further improve the fracture toughness, wear resistance, and fracture resistance of the cBN sintered body.

[0095] Intensity I of the diffraction peak attributed to the cBN (111) plane A The intensity of the diffraction peak attributed to the W2B (211) plane for B The ratio of [I B / I A ] is preferably 0.05 to 0.80, more preferably 0.10 to 0.60, and even more preferably 0.20 to 0.45, in order to further improve the fracture toughness, wear resistance, and fracture resistance of the cBN sintered body.

[0096] Intensity I of the diffraction peak attributed to the cBN (111) plane A Regarding, the intensity I of the diffraction peak attributable to the W2CoB2 (211) plane and the diffraction peak attributable to the W2CoB2 (310) plane, whichever has a larger intensity c The ratio of [I c / I A ] is preferably 0.20 to 1.50, more preferably 0.30 to 1.00, and even more preferably 0.40 to 0.80, in order to further improve the fracture toughness, wear resistance, and fracture resistance of the cBN sintered body.

[0097] The intensity I of the diffraction peak attributable to the plane W2CoB2 (211) and the diffraction peak attributable to the plane W2CoB2 (310), whichever has a larger intensity c The intensity of the diffraction peak attributed to the W2B (211) plane for B The ratio of [I B / I C ] is preferably 0.20 to 1.00, more preferably 0.30 to 0.70, and even more preferably 0.40 to 0.50, in order to further improve the fracture toughness, wear resistance, and fracture resistance of the cBN sintered body.

[0098] Intensity I of the diffraction peak attributed to the cBN (111) plane A For, the intensity of the diffraction peak I attributed to the (110) plane of metal W D The ratio of [I D / I A ] is preferably 0.10 or less, more preferably 0.01 or less, even more preferably 0.001 or less, and particularly preferably 0, in order to further improve the fracture toughness, wear resistance, and fracture resistance of the cBN sintered body.

[0099] The content of W in the cBN sintered body of the present embodiment is preferably 4.00 to 15.00 mass%, more preferably 4.50 to 10.00 mass%, even more preferably 5.00 to 8.50 mass%, and even more preferably 5.20 to 7.00 mass%, from the perspective of further improving the wear resistance and fracture resistance of the cBN sintered body.

[0100] In addition, in this specification, the content of W and elements such as Co, Ti, and Al described below is measured by energy dispersive X-ray spectroscopy (EDS), and specifically, can be measured by the method described in the examples.

[0101] The content of Co in the cBN sintered body of the present embodiment is preferably 0.05 to 2.00 mass%, more preferably 0.10 to 1.50 mass%, even more preferably 0.30 to 1.00 mass%, and even more preferably 0.50 to 0.80 mass%, in order to further improve the wear resistance and fracture resistance of the cBN sintered body.

[0102] One or more selected from the group consisting of Ti carbides, Ti nitrides, Ti carbonitrides, and Ti borides contained in the binder phase can be adjusted according to the type of binder used, and in the present embodiment, it is preferable to contain one or more selected from the group consisting of Ti nitrides and Ti borides, and more preferable to contain one or more selected from the group consisting of TiN and TiB2.

[0103] The Ti content in the cBN sintered body of the present embodiment is preferably 4.00 to 15.00 mass%, more preferably 6.00 to 13.00 mass%, and even more preferably 8.00 to 12.00 mass%, in order to further improve the wear resistance and fracture resistance of the cBN sintered body.

[0104] It is preferable that the binder phase further contains one or more selected from the group consisting of Al nitrides, Al borides, and Al oxides. One or more selected from the group consisting of Al nitrides, Al borides, and Al oxides can be adjusted according to the type of binder used, and in the present embodiment, it is preferable to contain one or more selected from the group consisting of Al nitrides and Al oxides, and more preferable to contain one or more selected from the group consisting of AlN and Al2O3.

[0105] The content of Al in the cBN sintered body of the present embodiment is preferably 1.00 to 6.00 mass%, more preferably 1.50 to 5.00 mass%, and even more preferably 2.00 to 4.00 mass%, in order to further improve the wear resistance and fracture resistance of the cBN sintered body.

[0106] Each compound constituting the bonding phase can be qualitatively identified from the XRD pattern of the cBN sintered body, just like the above W2B, W2CoB2, etc.

[0107] The bonding phase may include compounds other than the W2B, W2CoB2, Ti compounds, and Al compounds described above. The bonding phase may include, for example, a complex oxide of Al and Ti; ZrB2, ZrB 12 , HfB2, HfB, HfB 12 , VB2, V3B4, V3B 12 Borides of Group 4–6 transition metal elements such as , VB, V5B6, V2B2, NbB2, Nb3B2, NbB, TaB2, Ta2B, Ta3B2, TaB, Ta3B4, CrB, CrB4, Cr2B, Cr2B3, Cr5B3, CrB2, MoB, Mo2B5, MoB4, Mo2B, MoB2, WB, WB4, etc.; ZrN x (0 <x≤1), Hf3N2, HfN x (0 <x≤1), Hf4N3, VN x (0 <x≤1), V2N, NbN, Nb4N3, Nb2N, TaN x (0 <x≤1), Ta3N5, Ta4N, Ta2N, Cr2N, CrN x (0 <x≤1), WN, W2N 등의 제4∼6족 천이 금속 원소의 질화물; 상기 서술한 화합물도 포함한 각 화합물의 상호 고용체; 등이 포함되어 있어도 된다. 단, cBN 소결체 중, Ti 및 W 이외의 제4∼6족 천이 금속 원소의 각각의 함유량은, 가능한 한 적은 것이 바람직하다. Ti 및 W 이외의 제4∼6족 천이 금속 원소의 각각의 함유량은, 바람직하게는 1,000질량ppm 이하, 보다 바람직하게는 100질량ppm 이하이다.

[0108] In addition, the cBN sintered body of the present embodiment may contain, for example, unavoidable impurities derived from the blended raw materials. Examples of such unavoidable impurities include Li, Mg, Ca, Al, Si, Ti, C, B, S, P, Ga, Co, Ni, Mn, Fe, Cl, W, compounds thereof, and may also include compounds that overlap with the above other compounds.

[0109] Vickers Hardness

[0110] The Vickers hardness of the cBN sintered body of the present embodiment is preferably 3,000 HV or higher, more preferably 3,200 HV or higher, even more preferably 3,300 HV or higher, even more preferably 3,400 HV or higher, and particularly preferably 3,450 HV or higher, from the perspective of being suitable for use in cutting workpieces of high hardness.

[0111] The Vickers hardness of the cBN sintered body of the present embodiment is preferably higher, but from the perspective of ease of manufacturing, it may be 5,000 HV or less, 4,000 HV or less, or 3,800 HV or less.

[0112] The Vickers hardness of the cBN sintered body can be measured by the method described in the example.

[0113] Thermal conductivity

[0114] The thermal conductivity of the cBN sintered body of the present embodiment is preferably 50.0 W / m·K or higher, more preferably 54.0 W / m·K or higher, even more preferably 55.0 W / m·K or higher, even more preferably 56.0 W / m·K or higher, and particularly preferably 58.0 W / m·K or higher, in order to further improve wear resistance and fracture resistance.

[0115] The thermal conductivity of the cBN sintered body of the present embodiment is preferably higher, but from the perspective of ease of manufacturing, it may be 70.0 W / m·K or less, 67.0 W / m·K or less, or 65.0 W / m·K or less.

[0116] The thermal conductivity of the cBN sintered body can be measured by the method described in the example.

[0117] [Method for manufacturing cBN sintered body]

[0118] The method for manufacturing a cBN sintered body according to the present embodiment is,

[0119] A binder grinding process in which a binder, which is a raw material forming the above-mentioned bonding phase, is ground in a container containing a grinding medium, and

[0120] A mixing process for obtaining a raw material mixture by mixing the binder after grinding and cubic boron nitride particles, and

[0121] The process includes a sintering process for obtaining a cubic boron nitride sintered body by pressurizing and heating the above raw material mixture, and

[0122] The grinding medium used in the above-mentioned binder grinding process is a method for manufacturing a cubic boron nitride sintered body containing WC.

[0123] Hereinafter, each process of the method for manufacturing the cBN sintered body of the present embodiment will be described.

[0124] <Binder Grinding Process>

[0125] The binder grinding process is a process of grinding a binder within a container that holds a grinding medium.

[0126] In the binder grinding process, the binder being ground preferably comprises a raw material containing Ti, and may consist only of a raw material containing Ti, or may be a mixture of a raw material containing Ti and a raw material other than a raw material containing Ti.

[0127] The raw material containing Ti may be a single element or a compound.

[0128] As raw materials containing Ti, TiN and TiAl3 are preferred, and containing both TiN and TiAl3 is more preferable. By using TiN and TiAl3 as raw materials containing Ti, TiN, AlN, Al2O3, TiB2, etc. can be produced in the bonded phase.

[0129] Average particle diameter (D) of raw material containing Ti provided to the binder grinding process 50 ) is preferably 30.0 μm or less, more preferably 25.0 μm or less, and even more preferably 20.0 μm or less, from the perspective that the desired particle size is easily obtained under suitable grinding conditions. Average particle diameter (D) of the raw material containing Ti 50 ) may be 0.1㎛ or larger, 0.3㎛ or larger, or 0.5㎛ or larger.

[0130] Average particle diameter (D) of TiN provided to the binder grinding process 50 ) is preferably 2.5 μm or less, more preferably 2.0 μm or less, and even more preferably 1.5 μm or less, in terms of the ease with which the desired particle size is obtained under suitable grinding conditions. Average particle diameter of TiN (D 50 ) may be 0.1㎛ or larger, 0.3㎛ or larger, or 0.5㎛ or larger.

[0131] Average particle diameter (D) of TiAl3 provided to the binder grinding process 50 ) is preferably 30.0 μm or less, more preferably 25.0 μm or less, and even more preferably 20.0 μm or less, in terms of the ease with which the desired particle size is obtained under suitable grinding conditions. Average particle diameter (D) of TiAl3 50 ) may be 1.0㎛ or larger, 5.0㎛ or larger, or 10.0㎛ or larger.

[0132] In the binder grinding process, the binder is ground in a container containing a grinding medium containing WC.

[0133] In the method for manufacturing a cBN sintered body according to the present embodiment, the binder is ground using a grinding medium containing WC, thereby including WC derived from the grinding medium in the raw material. The said WC is transformed into W2B, W2CoB2, etc. through a subsequent sintering process, thereby obtaining the cBN sintered body according to the present embodiment. Therefore, in the manufacturing method of the present embodiment, it is desirable to adjust the conditions of the binder grinding process so that a desirable amount of W2B and W2CoB2 is formed. For example, by making the grinding conditions in the binder grinding process harsher than conventional conditions, a large amount of fine WC derived from the grinding medium is included in the raw material, and W2B and W2CoB2 are easily formed.

[0134] The grinding medium may contain WC, but it is preferable to contain Co along with WC, and it is more preferable to be a cemented carbide alloy containing WC and Co.

[0135] The content of WC in the grinding medium is preferably 70 to 97 mass%, more preferably 76 to 92 mass%, and even more preferably 82 to 88 mass%.

[0136] The content of Co in the grinding medium is preferably 3 to 30 mass%, more preferably 8 to 24 mass%, and even more preferably 12 to 18 mass%.

[0137] The grinding method in the binder grinding process is not particularly limited as long as a grinding medium is used, and examples include ball mills and rod mills, but a ball mill is preferred from the perspective of productivity. That is, the grinding medium is preferably a ball used in a ball mill. Also, the ball mill in this specification may be referred to as a bead mill.

[0138] The ball mill may be a rotary ball mill, a vibrating ball mill, or a combination of rotary and vibrating, but a rotary ball mill is preferred from the perspective of productivity. The rotary ball mill may be a conventional self-rotating ball mill or a planetary ball mill.

[0139] When using a ball mill, it is preferable that the material of the mill pot also contains WC, more preferable that it contains Co along with WC, and even more preferable that it is a cemented carbide alloy containing WC and Co. The suitable content of WC and Co in the material of the mill pot is the same as that of the grinding medium.

[0140] The diameter of the balls used in the ball mill is preferably 0.1 to 20.0 mm, more preferably 0.5 to 10.0 mm, and even more preferably 1.0 to 5.0 mm.

[0141] Grinding by a ball mill may be either dry or wet, but wet grinding is preferred from the perspective of enabling more uniform grinding. Examples of dispersion media for wet grinding include acetone, hexane, 2-propanol, ethanol, heptane, etc. Among these, acetone is preferred. One type of dispersion media may be used alone, or two or more types may be used in combination.

[0142] When the grinding of the binder grinding process is performed in a wet manner, the content of the grinding target in the slurry obtained by mixing the grinding target containing the binder with a dispersion medium is preferably 10 to 70 mass%, more preferably 20 to 60 mass%, and even more preferably 30 to 50 mass%.

[0143] Grinding may be performed in an air atmosphere or in an inert gas atmosphere such as N2 gas.

[0144] When using a rotary ball mill in the binder grinding process, it is desirable to appropriately determine conditions such as grinding time, rotational speed, ball filling amount, and filling amount of the material to be ground, depending on the grinding scale, desired particle size, etc.

[0145] In the binder grinding process using a rotary ball mill, the grinding time of the ball mill may be, for example, 3 to 7 hours.

[0146] In a binder grinding process using a rotary ball mill, the rotational speed of the ball mill may be, for example, 150 to 300 rpm.

[0147] In a binder grinding process using a rotary ball mill, the amount of balls fed into the mill pot may be, for example, 15 to 35 volume% relative to the internal volume of the mill pot.

[0148] In a binder grinding process using a rotary ball mill, the amount of material to be ground and fed into the mill pot may be, for example, 20 to 40 volume percent relative to the internal volume of the mill pot.

[0149] In the grinding process, grinding may be performed only once, or, if necessary, two or more times.

[0150] Average particle diameter (D) of the binder after grinding obtained by the binder grinding process 50 ) is preferably 0.10 to 2.5 μm, more preferably 0.30 to 1.8 μm, and even more preferably 0.50 to 1.1 μm from the perspective of homogenizing the composition of the cBN sintered body.

[0151] Mixing Process

[0152] The mixing process is a process of obtaining a raw material mixture by mixing the binder and cBN particles after the above-mentioned grinding.

[0153] cBN particles are suitably used, for example, cBN with a purity of 99.9% or higher obtained from ultra-high pressure high temperature synthesis at 3 GPa or higher and 1,200°C or higher, which is finely ground to adjust the particle diameter and particle shape.

[0154] Desirable average particle diameter (D) of cBN particles 50 The explanation for ) is as described in the section of the explanation of [cBN] above.

[0155] The amount of cBN particles is preferably such that the cBN content in the resulting cBN sintered body falls within the suitable range mentioned above.

[0156] In the mixing process, it is preferable to mix the raw materials, including each binder pulverized material and cBN particles, in a container containing a pulverizing medium.

[0157] The mixing method in the mixing process can be the same as the grinding method exemplified in the binder grinding process, and the preferred embodiment is also the same. That is, mixing in the mixing process is preferably performed by a rotary ball mill. When mixing by a rotary ball mill is performed wet, the content of the raw material in the slurry obtained by mixing the raw material and the dispersion medium is preferably 50 to 80 mass%, more preferably 55 to 75 mass%, and even more preferably 60 to 70 mass%.

[0158] Mixing may be performed under an air atmosphere or under an inert gas atmosphere such as N2 gas.

[0159] When using a rotary ball mill in a mixing process, it is desirable to appropriately determine conditions such as mixing time, rotation speed, ball filling amount, and filling amount of the material to be mixed, depending on the mixing scale, etc.

[0160] In a mixing process using a rotary ball mill, the mixing time of the ball mill may be, for example, 2 to 6 hours.

[0161] In a mixing process using a rotary ball mill, the rotational speed of the ball mill may be, for example, 100 to 200 rpm.

[0162] In a mixing process using a rotary ball mill, the amount of balls fed into the mill pot may be, for example, 25 to 40 volume percent relative to the internal volume of the mill pot.

[0163] In a mixing process using a rotary ball mill, the amount of raw material fed into the mill pot may be, for example, 40 to 60 volume percent relative to the internal volume of the mill pot.

[0164] <Heat Treatment Process>

[0165] The raw material mixture obtained by the mixing process may be subjected to heat treatment for degassing as needed, and the raw material mixture after heat treatment may be used.

[0166] The temperature of the heat treatment for degassing is preferably 800°C or lower, in terms of the uniform progress of the reaction sintering of the bonding phase and the densification of the sintered body.

[0167] In addition, from the perspective of sufficiently removing impurity components such as organic matter and densifying the cBN sintered body, it is desirable that the heat treatment temperature be 500℃ or higher.

[0168] From the above perspective, the heat treatment temperature is more preferably 550 to 750°C, and even more preferably 600 to 700°C.

[0169] From the perspective of efficiently performing degassing, it is preferable to perform the heat treatment under a vacuum atmosphere, and the pressure is 1.0 × 10⁻⁶ -3 It is desirable to perform this at Pa or lower.

[0170] The time for heat treatment is appropriately set according to the amount of raw material mixture to be treated, the type of dispersion medium used in the mixing process, etc., but is typically 0.1 to 10 hours, and preferably 1 to 3 hours.

[0171] Sintering Process

[0172] The sintering process is a process of obtaining a cubic boron nitride sintered body by pressurizing and heating the raw material mixture obtained from the mixing process. Additionally, the raw material mixture obtained from the mixing process may be the raw material mixture obtained after heat treatment in the heat treatment process, or it may be a raw material mixture obtained without performing the heat treatment process.

[0173] The maximum temperature in the pressurized heat treatment is preferably 1,200 to 1,600°C, more preferably 1,250 to 1,550°C, and even more preferably 1,300 to 1,500°C, in terms of densification of the cBN sintered body.

[0174] The maximum pressure in the pressurized heat treatment is preferably 3.0 GPa or higher, more preferably 3.5 GPa or higher, and even more preferably 4.0 GPa or higher, from the perspective of densification of the cBN sintered body. The maximum pressure in the pressurized heat treatment may be 7.0 GPa or lower, 6.0 GPa or lower, or 5.0 GPa or lower.

[0175] In order to suppress oxidation of the raw material mixture during pressurized heat treatment and to produce a desired cBN sintered body, it is desirable to use an inert gas atmosphere during pressurized heat treatment. Examples of inert gases include Ar gas and N2 gas. These gases may be used individually or in combination of two or more types.

[0176] [Tools]

[0177] The tool of the present embodiment includes the cBN sintered body of the present embodiment as a constituent material.

[0178] As described above, the cBN sintered body of the present embodiment is a material suitable for tools, particularly for cutting or grinding tools, because it has high hardness and excellent wear resistance and fracture resistance.

[0179] Examples

[0180] The present embodiment is described below based on examples, but the present embodiment is not limited to examples.

[0181] [Average particle diameter (D 50 ), 10% particle diameter (D 10 ) and 90% particle diameter (D 90 Measurement method of )

[0182] The particle size distribution was measured using a particle size analysis measuring device ("LA-920", manufactured by Horiba Seisakusho Co., Ltd.). Then, in the obtained particle distribution, the 10% particle diameter (D) at which the cumulative volume is 10% 10 ), average particle diameter (D 50 ), and 90% particle diameter (D) with a cumulative volume of 90% 90 Measured ).

[0183] [Method for Calculating Porosity of cBN Particles]

[0184] The porosity of the cBN particles was calculated from the aforementioned Ouchiyama formula.

[0185] In addition, the particle diameter (D in Ouchiyama's formula) i ) is, the above [average particle diameter (D 50 The particle size of the cBN particles obtained from the measurement method of ) is the average particle diameter (upper bar attached D), and the above [average particle diameter (D 50 Average particle diameter (D) of cBN particles obtained from the measurement method of ) 50 It is the ratio of the number of particles of each particle diameter (f i ) and the mass ratio of particles of each particle diameter (w i ) is a value obtained from the particle size distribution of cBN particles, and the porosity (ε when there is a single particle diameter) 0i ) is a value calculated by assuming that cBN particles of each particle size are spheres. When two or more types of cBN particles are mixed, each of the above parameters can be calculated from the particle size distribution and mixing amount of each cBN particle.

[0186] [Method for measuring cBN content and ferret diameter]

[0187] In each example, the cBN sintered body samples obtained for evaluation were used as measurement targets, and reflected electron images were captured at a magnification of 5,000x using a scanning electron microscope (SEM) ("S-5500", manufactured by Hitachi High-Tech Co., Ltd.). The captured images contained black, white, and gray areas, and as a result of performing energy dispersive X-ray spectroscopy (EDS) on each part, it was confirmed that the black area was cBN and the white and gray areas were the bonding phases.

[0188] The captured image was binarized using image processing software, and the black area representing cBN and the white area representing the combined image were identified. The ratio of the black area to the entire field of view of the binarized image was calculated, and the arithmetic mean of the three fields of view was considered as the cBN content (unit: volume%).

[0189] As a representative example, the reflected electron image of the sintered body of Example 1 is shown in FIG. 3, and the binarized processed image thereof is shown in FIG. 4. In addition, the size of one field of view is 25.0 μm in width and 17.4 μm in height, and the total area of ​​three fields of view is 1305.0 μm. 2 am.

[0190] In addition, in the entire field of view of the binarized processing image of the reflected electron image taken at a magnification of 5,000x, all measurable ferret diameters of cBN were obtained by image processing software, and the arithmetic mean of these values ​​was set as the ferret diameter of cBN (unit: μm).

[0191] [Elemental Analysis]

[0192] Energy-dispersive X-ray spectroscopy (EDS) was performed on the evaluation cBN sintered body samples obtained in each example, and the elemental concentrations of B, N, O, C, Al, Ti, Co, and W in the cBN sintered bodies were measured. In addition, the elemental concentrations were measured across the entire field of view observed under the following conditions and taken as the average of 10 fields of view. The EDS measurement conditions are shown below.

[0193] Measuring device: JSM-6510LA (manufactured by Nihon Denshi Co., Ltd.)

[0194] EDS Analysis Software: Analysis Station (Manufactured by Nihon Denshi Co., Ltd.)

[0195] Acceleration voltage: 20.0kV (Irradiation current: 1.00000nA)

[0196] Magnification: 2,000x

[0197] Energy range: 0-20 keV

[0198] [Analysis Method for Sintered Body Composition]

[0199] The cBN sintered body samples obtained for evaluation in each example were used as measurement targets, and XRD measurements were performed using an X-ray diffraction device ("X'pert PRO", manufactured by Panalytical). The measurements were performed under conditions of CuKα rays, output voltage 40 kV, output current 40 mA, sampling width 0.0167°, scan speed 0.4178° / s, and measurement range 2θ = 10 to 80°.

[0200] The measured XRD patterns were qualitatively compared with an inorganic material database using PANalytical's software "X'pert High Score Plus". The components detected by XRD analysis are shown in "Sintered Body Composition" of Table 1.

[0201] [Method for Measuring Diffraction Peak Intensity Ratio]

[0202] In the XRD pattern in the above [Method for Analyzing Sintered Body Composition], the diffraction peak intensity of the cBN (111) plane near 2θ=43.30° is I A , the intensity of the diffraction peak attributed to the W2B (211) plane near 2θ=40.90° is I B , the intensity of the diffraction peak attributable to the W2CoB2 (211) plane and the diffraction peak attributable to the W2CoB2 (310) plane near 2θ=43.10°, the intensity of the diffraction peak with the greater intensity is I c , the diffraction peak intensity attributed to the (110) plane of metal W near 2θ=40.30° I D With respect to, the intensity ratio of each diffraction peak [I B / I A ], [I C / I A ], [I B / I C ], [I D / I A ] and [( I B +I C ) / I A ] were calculated respectively.

[0203] As a representative example, the range of 2θ=39° to 44° of the XRD pattern of the cBN sintered body obtained in Example 1 is shown in FIG. 1, and the range of 2θ=39° to 44° of the XRD pattern of the cBN sintered body obtained in Comparative Example 2 is shown in FIG. 2.

[0204] [Manufacture of Cubic Boron Nitride Sintered Body]

[0205] Examples 1 to 3

[0206] (Binder grinding process)

[0207] TiN (average particle diameter (D 50 )=1.2㎛) 7.7g, TiAl3(average particle diameter (D 50 2.6g of (19.8㎛), 21ml of dispersion medium (acetone), and 161g of balls were placed into the mill pot of a planetary ball mill (product name "Planetary Ball Mill", manufactured by Fritz Co., Ltd.) and ground under the following grinding conditions. In addition, both the mill pot and balls of the planetary ball mill are made of cemented carbide (composition: WC content is about 85 mass%, Co content is about 15 mass%), the height of the cylindrical mill pot is 23mm, the inner diameter is Φ65mm, and the diameter of the balls is 1.3mm.

[0208] <Binder Grinding Conditions>

[0209] · Raw material (slurry) filling amount: Approximately 32 volume% relative to the internal volume of the mill pot

[0210] · Ball filling amount: Approximately 24 volume% relative to the internal volume of the mill pot

[0211] · Atmosphere: Air atmosphere

[0212] · Rotation speed: 270 rpm

[0213] · Grinding time: 5 hours

[0214] (Mixing process of cBN particles and binder)

[0215] 31g of cBN particles listed in Table 1, 8ml of dispersion medium (acetone), and 54g of balls (ball diameter 3.0mm) were added to the mill pot after the above binder grinding process was completed, and mixed under the following mixing conditions to obtain a slurry of the raw material mixture. The material of the balls is the same as the material of the balls used in the binder grinding process.

[0216] <cBN 입자와 결합재의 혼합 조건>

[0217] · Raw material (slurry) filling amount: Approximately 54 volume% relative to the internal volume of the mill pot

[0218] · Ball filling amount: Approximately 32 volume% relative to the internal volume of the mill pot

[0219] · Atmosphere: N2 gas atmosphere

[0220] · Rotation speed: 140 rpm

[0221] · Mixing time: 4 hours

[0222] Also, the details of the cBN particles (1) to (3) shown in Table 1 are as follows.

[0223] cBN particles (1): 10% particle diameter (D 10 )=0.56㎛, average particle diameter (D 50 )=0.86㎛, 90% particle diameter (D 90 )=1.49㎛

[0224] cBN particles (2): 10% particle diameter (D 10 )=1.92㎛, average particle diameter (D 50 )=2.93㎛, 90% particle diameter (D 90 )=4.31㎛

[0225] cBN particles (3): 10% particle diameter (D 10 )=3.06㎛, average particle diameter (D 50 )=4.60㎛, 90% particle diameter (D 90 )=6.42㎛

[0226] (Heat treatment process)

[0227] The slurry obtained above is dried by standing at 70°C for 5 hours under an N2 gas atmosphere, and then 1.0 × 10 -3 Degassing was performed by heat treatment at 650°C for 0.5 hours under a vacuum atmosphere of Pa or less, and a heat-treated powder was obtained.

[0228] (Sintering process)

[0229] Under an N2 gas atmosphere, the above heat-treated powder was laminated onto a cemented carbide support plate, and then subjected to pressure heat treatment at 4.5 GPa and 1,500°C for 1 hour to produce a cBN sintered body (diameter approximately 30 mm, thickness approximately 4 mm). The upper surface of the cBN sintered body (the lower surface in contact with the cemented carbide support plate) was ground with a #400 diamond grinding wheel to prepare a cBN sintered body sample for evaluation.

[0230] Example 4

[0231] (Binder grinding process)

[0232] TiN (average particle diameter (D 50 )=1.2㎛) 0.9g, TiC(average particle diameter (D 50 )=0.70㎛) 5.8g, TiAl3(average particle diameter (D 50 3.6g of (=19.8㎛), 21ml of dispersion medium (acetone), and 161g of balls were placed into the mill pot of a planetary ball mill (product name "Planetary Ball Mill", manufactured by Fritz Co., Ltd.) and ground under the same conditions as the binder grinding conditions in Example 1. In addition, the specifications of the planetary ball mill and balls are the same as those in Example 1.

[0233] (Mixing process of cBN particles and binder)

[0234] 31g of cBN particles listed in Table 1, 8ml of dispersion medium (acetone), and 54g of balls (ball diameter 3.0mm) were added to the mill pot after the above binder grinding process was completed, and mixed under the same conditions as the mixing conditions of the cBN particles and binder in Example 1 to obtain a slurry of the raw material mixture. The material of the balls is the same as the material of the balls used in the binder grinding process.

[0235] (Heat treatment process and firing process)

[0236] Using the slurry obtained above, a cBN sintered body sample for evaluation was obtained by performing a heat treatment process and a sintering process under the same conditions as in Example 1.

[0237] Example 5

[0238] (Binder grinding process)

[0239] TiN (average particle diameter (D 50 )=1.2㎛) 9.3g, TiAl3(average particle diameter (D 50 3.1g of (=19.8㎛), 21ml of dispersion medium (acetone), and 161g of balls were placed into the mill pot of a planetary ball mill (product name "Planetary Ball Mill", manufactured by Fritz Co., Ltd.) and ground under the same conditions as the binder grinding conditions in Example 1. In addition, the specifications of the planetary ball mill and balls are the same as those in Example 1.

[0240] (Mixing process of cBN particles and binder)

[0241] 28.9 g of cBN particles listed in Table 1, 8 ml of dispersion medium (acetone), and 54 g of balls (ball diameter 3.0 mm) were added to the mill pot after the above binder grinding process was completed, and mixed under the same conditions as the mixing conditions of the cBN particles and binder in Example 1 to obtain a slurry of the raw material mixture. The material of the balls is the same as the material of the balls used in the binder grinding process.

[0242] (Heat treatment process and firing process)

[0243] Using the slurry obtained above, a cBN sintered body sample for evaluation was obtained by performing a heat treatment process and a sintering process under the same conditions as in Example 1.

[0244] Example 6

[0245] (Binder grinding process)

[0246] TiN (average particle diameter (D 50 )=1.2㎛) 10.8g, TiAl3(average particle diameter (D 50 3.7g of (=19.8㎛), 21ml of dispersion medium (acetone), and 161g of balls were placed into the mill pot of a planetary ball mill (product name "Planetary Ball Mill", manufactured by Fritz Co., Ltd.) and ground under the same conditions as the binder grinding conditions in Example 1. In addition, the specifications of the planetary ball mill and balls are the same as those in Example 1.

[0247] (Mixing process of cBN particles and binder)

[0248] 26.8 g of cBN particles listed in Table 1, 8 ml of dispersion medium (acetone), and 54 g of balls (ball diameter 3.0 mm) were added to the mill pot after the above binder grinding process was completed, and mixed under the same conditions as the mixing conditions of the cBN particles and binder in Example 1 to obtain a slurry of the raw material mixture. The material of the balls is the same as the material of the balls used in the binder grinding process.

[0249] (Heat treatment process and firing process)

[0250] Using the slurry obtained above, a cBN sintered body sample for evaluation was obtained by performing a heat treatment process and a sintering process under the same conditions as in Example 1.

[0251] Example 7

[0252] (Binder grinding process)

[0253] TiN (average particle diameter (D 50 )=1.2㎛) 12.3g, TiAl3(average particle diameter (D 50 4.2g of (=19.8㎛), 21ml of dispersion medium (acetone), and 161g of balls were placed into the mill pot of a planetary ball mill (product name "Planetary Ball Mill", manufactured by Fritz Co., Ltd.) and ground under the same conditions as the binder grinding conditions in Example 1. In addition, the specifications of the planetary ball mill and balls are the same as those in Example 1.

[0254] (Mixing process of cBN particles and binder)

[0255] 24.8 g of cBN particles listed in Table 1, 8 ml of dispersion medium (acetone), and 54 g of balls (ball diameter 3.0 mm) were added to the mill pot after the above binder grinding process was completed, and mixed under the same conditions as the mixing conditions of the cBN particles and binder in Example 1 to obtain a slurry of the raw material mixture. The material of the balls is the same as the material of the balls used in the binder grinding process.

[0256] (Heat treatment process and firing process)

[0257] Using the slurry obtained above, a cBN sintered body sample for evaluation was obtained by performing a heat treatment process and a sintering process under the same conditions as in Example 1.

[0258] Comparative Example 1

[0259] In Example 1, cBN sintered bodies and cBN sintered body samples for evaluation were obtained in the same manner as in Example 1, except that the type of cBN particles was changed to the type listed in Table 1, the amount of cBN particles was changed to 26.1g, the amount of TiN was changed to 9.1g, and the amount of TiAl3 was changed to 4.9g, and the amount of balls added in the binder grinding process was changed to 107g and the grinding time in the binder grinding process was changed to 4 hours.

[0260] Comparative Example 2

[0261] In Example 1, a cBN sintered body and a cBN sintered body sample for evaluation were obtained in the same manner as in Example 1, except that the amount of balls added in the binder grinding process was changed to 107g, the ball diameter to 3.0mm, and the grinding time in the binder grinding process to 4 hours, and no additional balls were added in the mixing process of cBN particles and binder.

[0262] Comparative Example 3

[0263] (Binder grinding process)

[0264] TiN (average particle diameter (D 50 )=1.2㎛) 14.4g, TiC(average particle diameter (D 50 )=0.70㎛) 4.2g, TiAl3(average particle diameter (D 50 7.4g of (19.8㎛), 15.3g of cBN particles listed in Table 1, 21ml of dispersion medium (acetone), and 107g of balls (ball diameter 3.0mm) were placed into the mill port of a planetary ball mill (product name "Planetary Ball Mill", manufactured by Fritz Co., Ltd.), and ground and mixed under the following conditions to obtain a slurry of the raw material mixture. In addition, the specifications of the planetary ball mill and balls are the same as those in Example 1.

[0265] <Grinding and Mixing Conditions>

[0266] · Raw material (slurry) filling amount: Approximately 54 volume% relative to the internal volume of the mill pot

[0267] · Ball filling amount: Approximately 24 volume% relative to the internal volume of the mill pot

[0268] · Atmosphere: Air atmosphere

[0269] · Rotation speed: 190 rpm

[0270] · Grinding and mixing time: 6 hours

[0271] (Heat treatment process and firing process)

[0272] Using the slurry obtained above, a cBN sintered body sample for evaluation was obtained by performing a heat treatment process and a sintering process under the same conditions as in Example 1.

[0273] [Evaluation Method]

[0274] For the cBN sintered body samples obtained for evaluation in each example, the following various evaluations were performed. The evaluation results are summarized in Table 1.

[0275] Vickers Hardness Measurement Method

[0276] In accordance with JIS Z 2244:2009, the product name “HMV-G21” (manufactured by Shimadzu Seisakusho Co., Ltd.) was used as the measuring device, and the Vickers hardness of the cBN sintered body samples for evaluation obtained in each example was measured under conditions of a load of 9.8 N, a holding time of 15 seconds, and 25°C.

[0277] Method for Measuring Thermal Conductivity

[0278] A sample for measuring thermal conductivity (thickness: 0.80 mm, diameter: 10.0 mmΦ) was cut from a cBN sintered body sample for evaluation, and the surface of the obtained sample was blackened with black spray. With the thickness direction of the sample set as the heat flow direction, the thermal diffusivity was measured using a laser flash analyzer (manufactured by NETZSCH, product name "LFA457"). In addition, the specific heat of the sample was measured using the same device, and the density of the sample was calculated from the dimensions and weight of the sample. From these results, the thermal conductivity in the thickness direction of the cBN sintered body sample for evaluation was calculated using the following formula.

[0279] Thermal conductivity (W / (m·K)) = Specific heat (J / (kg·K)) × Density (kg / ㎥) × Thermal diffusivity (㎡ / sec)

[0280] Method for Measuring Fracture Toughness Values

[0281] The fracture toughness value was obtained by the IF method (indenter indentation method) in accordance with JIS R 1607:2015 “Room temperature fracture toughness test method for fine ceramics”. Using the product name “HMV-G21” (manufactured by Shimadzu Seisakusho Co., Ltd.) as the measuring device, a fracture toughness test was performed on 10 cBN sintered samples for evaluation under conditions of a maximum load of 9.8 N, an indenter indentation time of 5 seconds, and 25°C, and the arithmetic mean value was taken as the fracture toughness value.

[0282] <Cutting Evaluation 1>

[0283] A cutting tool conforming to ISO standard CNGA120404 was fabricated from the cBN sintered body obtained in each example. Using the obtained cutting tool, a cutting test was performed on the workpiece under the following cutting conditions. The number of machining operations was set to a maximum of 1,500, and the number of operations until the cutting tool failed was used as an indicator of failure resistance. In addition, for the cases where the number of operations reached 1,500, the amount of wear on the cutting tool after 1,500 operations was measured.

[0284] (Cutting conditions)

[0285] · Cutting speed: 145 m / min

[0286] · Machining allowance: Φ0.33mm

[0287] · Feed rate: 0.20 (mm / rev)

[0288] · Type of workpiece: Austenitic sintered alloy

[0289] · Test environment temperature: 25℃

[0290] <Cutting Evaluation 2>

[0291] A cutting tool conforming to ISO standard CNGA120404 (edge ​​shape: sharp edge) was manufactured from the cBN sintered body obtained in each example. Using the obtained cutting tool, a cutting test was performed on a workpiece under the following cutting conditions, and the amount of VB wear (mm) of the cutting tool was measured after the cutting evaluation.

[0292] (Cutting conditions)

[0293] · Cutting method: Continuous cutting (dry)

[0294] · Cutting speed: 400 m / min

[0295] · Sheath: 0.2mm

[0296] · Feed rate: 0.2 (mm / rev)

[0297] · Processing distance: 330m / pass

[0298] · Workpiece type: FC250 (Round bar of cast iron, hardness HB190)

[0299] · Test environment temperature: 25℃

[0300] <Cutting Evaluation 3>

[0301] A cutting tool conforming to ISO standard CNGA120404 (edge ​​shape: sharp edge) was manufactured from the cBN sintered body obtained in each example. Using the obtained cutting tool, a cutting test was performed on a workpiece under the following cutting conditions, and the number of intermittent impacts until the cutting tool failed was measured.

[0302] (Cutting conditions)

[0303] · Cutting method: Intermittent cutting (dry)

[0304] · Cutting speed: 150 m / min

[0305] · Sheath: 0.2mm

[0306] · Feed rate: 0.15 (mm / rev)

[0307] · Processing distance: 150m / pass

[0308] · Workpiece type: SCM415 (8 grooves) (Quenched steel, hardness HRC62~60)

[0309] · Test environment temperature: 25℃

[0310]

[0311] In Table 1, "ND" means that it was the detection limit.

[0312] In Table 1, "NE" means that no evaluation was conducted.

[0313] From Table 1, it can be seen that the cBN sintered bodies of Examples 1 to 7 of the present embodiment have excellent fracture resistance.< / cbn>

Claims

Claim 1 A cubic boron nitride sintered body having cubic boron nitride and a binder phase which is the remainder of the cubic boron nitride, wherein the content of the cubic boron nitride is 50.0 to 90.0 volume%, and the binder phase contains one or more selected from the group consisting of Ti carbides, Ti nitrides, Ti carbonitrides, and Ti borides, and one or more selected from the group consisting of W2B and W2CoB2, and in the X-ray diffraction pattern of the cubic boron nitride sintered body using CuKα rays as a source, the intensity of the diffraction peak attributed to the (111) plane of the cubic boron nitride is I A , the intensity of the diffraction peak attributed to the (211) plane of the above W2B is I B , the intensity of the diffraction peak attributable to plane (211) and plane (310) of the above W2CoB2, the intensity of the diffraction peak with the greater intensity is I c When said, the above I A Regarding, the above I B and the above I C The ratio of the sum of [(I B +I C ) / I A ] is 0.25 or higher, and the above-mentioned binding phase is a cubic boron nitride sintered body containing W2CoB2. Claim 2 A cubic boron nitride sintered body according to claim 1, having a W content of 4.00 to 15.00 mass%. Claim 3 In claim 1 or 2, the binding phase is a cubic boron nitride sintered body further containing W2B. Claim 4 In claim 3, the above I C Regarding the above I B The ratio of [I B / I C Cubic boron nitride sintered body with ] 0.20 to 1.

00. Claim 5 In claim 1 or 2, the average particle diameter (D 50 A cubic boron nitride sintered body containing two or more different types of cubic boron nitride particles. Claim 6 A cubic boron nitride sintered body having a thermal conductivity of 50.0 W / m·K or higher, according to claim 1 or 2. Claim 7 A tool comprising a cubic boron nitride sintered body described in claim 1 or 2 as a constituent material. Claim 8 In claim 7, a tool for cutting or grinding. Claim 9 A method for manufacturing a cubic boron nitride sintered body as described in claim 1 or 2, comprising: a binder grinding process in which a binder, which is a raw material forming the binder phase, is ground in a container containing a grinding medium; a mixing process in which the binder after grinding and cubic boron nitride particles are mixed to obtain a raw material mixture; and a sintering process in which the raw material mixture is subjected to pressure heat treatment to obtain a cubic boron nitride sintered body, wherein the grinding medium used in the binder grinding process contains WC.

Citation Information

Patent Citations

  • Cutting tool and surface-coated cutting tool utilizing cubic crystal boron nitride based ultrahigh-pressure sintered body as tool base body

    JP2014083664A

  • Composite sintered compact for cutting tool, and cutting tool utilizing the same

    JP2017132679A

  • Composite sintered body for cutting tool and cutting tool using the same

    JP2017165637A

  • Coated sintered cbn

    WO2011129422A1

  • cBN SINTERED MATERIAL TOOL AND COATED cBN SINTERED MATERIAL TOOL

    WO2012105710A1